ANALISIS KADAR NITRIT PADA SOSIS SAPI KEMASAN YANG BEREDAR DI PASAR TRADISIONAL KOTA BANDAR LAMPUNG SECARA SPEKTROFOTOMETRI UV-VIS - Samsuar Samsuar; Akhmad Rokiban; Dodo Hardoyo (Fakultas MIPA Universitas Tulang Bawang Lampung, 2020)
Abstract The use of nitrite as a preservative and provider of the stable red color, aroma as well as taste for the meat is allowed within processed meat products, such as beef sausage. However, it should be noted that its use does not exceed the maximum permitted limit so as not to negatively impact human health. Excess nitrite in the human body can cause acute poisoning, namely methemoglobinemia and chronic poisoning as a result of the formation of carcinogenic nitrosamine derivatives. This research aims to determine whether the levels of nitrite contained in the packaged beef sausage distributed in the traditional market of Bandar Lampung is in accordance with the regulations of The Indonesia Food and Drug Authority or Indonesia FDA No. 36 of 2013 which is not more than 30 mg/kg. The analysis of nitrite levels in the sample was carried out using with UV-Vis Spectrophotometry method based on diazotation reaction between nitric acid and sulfanilamide forming diazonium salts. The products were then reacted again with naphthyl ethylenediamine to form a purplish red compound whose absorbance was measured at a wavelength 0f 543,8 nm. From the results of the analytical methods validation, it was obtained that the value of the correlation coefficient was 0,9997, the coefficient of determination 0,9994, the coefficient of variation 1,2121%, the range of percent recovery between 98,630-101,240%, and the detection and the quantitation limit respectively at 0,0187 ppm and 0,0623 ppm. This indicates that all test parameters meet the requirements for their use. The result of determining the average levels of nitrite in the samples show that there were two samples that had levels exceeding the maximum allowed limit, i.e sampel C=40,407 mg/kg and sample D=33,181mg/kg while sample A=18,963 mg/kg, sample B=9,427 mg/kg, sample E=9,423 mg/kg and sample F=8,689 mg/kg did not exceed the maximum allowed limit. Keywords: Beef Sausage, Nitrite, UV-Vis Spectrophotometry, Method AnalysisValidation